Morphogenesis in Candida albicans() - Whiteway, Malcolm (Annu Rev Microbiol, 2007)
Candida albicans is termed a dimorphic fungus because it proliferates in either a yeast form or a hyphal form. The switch between these forms is the result of a complex interplay of external and internal factors and is coordinated in part by polarity-regulating proteins that are conserved among eukaryotic cells. However, yeast and hyphal cells are not the only morphological states of C. albicans. The opaque form required for mating, the pseudohyphal cell, and the chlamydospore represent distinct cell types that form in response to specific genetic or environmental conditions. In addition, hyperextended buds can form as a result of various cell cycle–related stresses. Recent studies are beginning to shed light on some of the molecular controls regulating the various morphogenetic forms of this fascinating human pathogen.